Kinetic modeling of ex-situ biomass catalytic pyrolysis. (2018) - Ipsakis, D.; Heracleous, E.; Gkinis, K.; Stefanidis, S.D.; Kalogiannis, K.G.; Lappas, A.A.
Abstract: Core objective of this study is the development and evaluation of a kinetic modeling strategy that is able to predict product yields (based on reaction lumps) during the ex-situ biomass catalytic pyrolysis. A series of experiments was initially performed in two interconnected reactors (thermal pyrolysis and catalytic upgrading) at the pilot-scale unit of the Laboratory of Environmental Fuels & Hydrocarbons in CPERI/CERTH. Specifically, the investigation of the effect of catalyst/biomass ratio and time-on-stream provided the required data towards estimating the main kinetic parameters of both thermal pyrolysis and catalytic upgrading steps. Both kinetic schemes feature a 1 st order dependence on biomass (thermal) and organic/bio-oil (catalytic) reactant mass fraction, respectively. Catalyst deactivation was evaluated via a time-dependent empirical function that was applied at each individual lump (CO, CO2, H2 O, organics/bio-oil and coke). Overall, it was identified that the applied kinetic model predicts accurately a) the reduction in the oxygen content of bio-oil with increased residence times (increase of the catalyst weight) and b) the increased coke formation with time-on-stream that deactivates the catalyst and deteriorates bio-oil quality (decrease of CO, H2 O mass yields and consequent increase of oxygen content in the final product)